Assessing the impact of a family nurse‐led intervention on young mothers' references to internal states. Issue 4 (11th February 2020) - Paine, Amy L.; Cannings‐John, Rebecca; Channon, Susan; Lugg‐Widger, Fiona; Waters, Cerith S.; Robling, Michael
ABSTRACT: A mother's propensity to refer to internal states during mother–child interactions is important for her child's developing social understanding. However, adolescent mothers are less likely to reference internal states when interacting with their children. We investigated whether young mothers' references to internal states are promoted by the Family Nurse Partnership (FNP) intervention, an intensive home‐visiting programme designed to support adolescent mothers in England. We also investigated family, maternal, and child factors associated with young mothers' references to inner states during interactions with their children. Adolescent mothers ( n = 483, aged ≤ 19 years when recruited in pregnancy) and their children participated in an observational substudy of a randomized controlled trial investigating the impact of FNP compared to usual care. Mother–child dyads were video‐recorded during free play, and mothers' speech was coded for use of internal state language (references to cognitions, desires, emotions, intentions, preferences, physiology, and perception). We found no differences in mothers' use of internal state language between the FNP and usual care groups. A sample‐wide investigation identified that other features of mothers' language and relationship status with the child's father were associated with internal state language use. Findings are discussed with reference to targeted interventions and implications for future research. RESUMEN: La tendencia de la madre a referirse a los estados internos durante las interacciones madre‐niño es importante para el desarrollo social cognitivo de su niño. Sin embargo, las madres adolescentes están menos propensas a referirse a los estados internos cuando interactúan con sus niños. Investigamos si la tendencia de las madres jóvenes a referirse a estados internos es promovida por la intervención de Asociación entre Familia y Enfermera (FNP), un programa intensivo de visitas a casa diseñado para apoyar a madres adolescentes en el Reino Unido. También investigamos factores de familia, maternos y del niño asociados con las interacciones de las jóvenes madres con sus niños. Las madres adolescentes (n = 483, edad ≤ 19 años) y sus niños participaron en un sub‐estudio de observación, un ensayo controlado al azar que investigaba el impacto de FNP comparado con el cuidado usual. Las díadas madre‐niño fueron grabadas en video durante el juego libre, y se codificó el habla de las madres en cuanto al uso del lenguaje de estados internos (referencias a cogniciones, deseos, emociones, intenciones, preferencias, fisiología y percepción). No encontramos diferencias en cuanto al uso del lenguaje de estados internos en las madres entre la FNP y los grupos de cuidado usual. Una muestra de investigación amplia identificó que otras características del lenguaje de las madres y condiciones de la relación con el padre del niño estaban asociadas con el uso del lenguaje de estados internos. Los resultados se discuten con referencia a intervenciones elegidas como objetivo e implicaciones para la futura investigación. RÉSUMÉ: La propension d'une mère à faire référence à ses états internes durant les interactions mère‐enfant est importante pour le développement social et cognitif de son enfant. Cependant, les mères adolescentes sont moins à même de faire référence à leurs états internes dans leur interaction avec leurs enfants. Notre étude a porté sur si la propension des jeunes mères à faire référence à leurs états internes est promue par l'intervention Partenariat Famille Infirmières (en anglais Family Nurse Partnership, soit FNP), un programme intensif de visite à domicile conçu afin de soutenir les mères adolescentes au Royaume Uni. Nous avons également étudié les facteurs familiaux, maternels, et liés aux enfants, liés aux interactions des jeunes mères avec leurs enfants. Les mères adolescentes (n = 483, âgés ≤ 19 ans) et leurs enfants ont participé à une sous‐étude observationnelle d'un essai contrôlé randomisé portant sur l'impact de la FNP comparé aux soins normaux. Les dyades mères‐enfant ont été filmées durant un jeu libre et les paroles des mères ont été codées pour son utilisation de langage d'état interne (références aux cognitions, désirs, émotions, intentions, préférences, physiologie et perception). Nous n'avons trouvé aucune différence dans l'utilisation des mères du langage d'état interne entre le groupe FNP et les groupes de contrôle. Une étude de l'échantillon a révélé que d'autres traits du langage des mères et du statut de la relation avec le père de l'enfant étaient liés à l'utilisation de langage de l'état interne. Les résultats sont discutés par rapport aux interventions ciblées et aux implications pour les recherches futures. ZUSAMMENFASSUNG: Beurteilung der Wirkungen einer von Familienpflegekräften geleiteten Intervention zur Bezugnahme junger Mütter auf innere Zustände Inwiefern sich eine Mutter bei den Interaktionen mit ihrem Kind auf innere Zustände bezieht, ist wichtig für die sozial‐kognitive Entwicklung des Kindes. Bei adoleszenten Müttern ist es jedoch weniger wahrscheinlich, dass sie bei der Interaktion mit ihren Kindern auf innere Zustände bezugnehmen. Wir haben untersucht, ob durch die Familienpflegekraft‐Partnerschaftsintervention (Family Nurse Partnership; FNP), ein intensives Hausbesuchsprogramm zur Unterstützung jugendlicher Mütter in Großbritannien, die Bezugnahme auf innere Zustände bei jungen Müttern gefördert werden kann. Ebenfalls untersuchten wir familiäre, mütterliche und kindliche Faktoren die mit der Interaktion junger Mütter mit ihren Kindern assoziiert sind. Die adoleszenten Mütter (n = 483, Alter ≤ 19 Jahre) und ihre Kinder nahmen an einer randomisierten kontrollierten Beobachtungsstudie teil, in der die Wirkung von FNP im Vergleich zur üblichen Betreuung untersucht wurde. Die Mutter‐Kind‐Dyaden wurden während eines freien Spiels auf Video aufgezeichnet und die Sprache der Mütter wurde hinsichtlich ihrer Bezüge auf interne Zustände codiert (Hinweise auf Kognitionen, Wünsche, Emotionen, Absichten, Vorlieben, Physiologie und Wahrnehmung). Zwischen der FNP‐Gruppe und der Gruppe mit der üblichen Betreuung konnten hinsichtlich der Bezugnahme auf innere Zustände keine Unterschiede beobachtet werden. Eine stichprobenweite Untersuchung ergab, dass andere sprachliche Merkmale der Mutter und der Beziehungsstatus zum Kindesvater mit dem Gebrauch von Bezügen auf innere Zustände zusammenhingen. Die Ergebnisse werden hinsichtlich gezielter Interventionen und Implikationen für zukünftige Forschung diskutiert. 抄録: 若年母親の内的状態に関する言及への家族看護師主導介入の影響を評価する 母子相互交流時における母親の内的状態について言及する傾向は、乳幼児の社会的認知の発達に重要である。しかしながら、若年母親は自分の子どもとの相互交流時に内的状態について言及する傾向が弱い。我々は、若年母親が内的状態を言及する傾向が、ナース・ファミリー・パートナーシップ(FNP)介入−それは、英国における若年母親を支援するために考案された集中的な家庭訪問プログラム−によって促進されるかどうかについて研究した。また、家族、母親と乳幼児それぞれの、若年母親の自分の子どもとの相互交流に関連する要素について研究した。若年母親(n = 483, 年齢 ≤ 19歳)とその子どもは普通のケアに比較してFNPの影響を調査するランダム化比較試験の観察下位研究に参加した。母子親子は自由遊び時を録画され、母親の発言は内的状態言語(認知、欲望、情緒、意図、好み、生理、知覚の言及)の使用についてコード化された。FNPと普通のケア群との間の母親の内的言語の使用に差異はなかった。サンプル全体の調査は母親の内的言語とは違う言語と子どもの父親との関係性は、内的状態言語の使用に関連していることが同定された。 結果は対象を絞った介入についての言及と今後の研究での予想される結果について討論している。 摘要: 母亲在母子互动过程中倾向于提及内在状态, 这对孩子的社会认知发展很重要。但是, 未成年母亲与其子女互动时却不太可能提及内在状态。我们调查了"家庭护士伙伴关系计划 (FNP) "的干预是否促进了未成年母亲提及内在状态的倾向, 该干预是一项旨在支持英国未成年母亲的密集的家访计划。我们还调查了与年轻母亲及其孩子互动有关的家庭、母亲和儿童方面的因素。未成年母亲 (n = 483, 年龄≤19岁) 及其子女参加了一项观察性的子研究, 这是一项随机对照试验, 调查FNP与常规护理相比的影响。在自由活动期间, 母子二人组被录制了视频, 母亲的谈话被编码, 以记录其使用内在状态的语言 (涉及到认知、欲望、情绪、意图、偏好、生理和感知) 。我们发现FNP组和常规护理组的母亲在使用内在状态语言方面没有差异。一项抽样调查显示, 母亲语言的其他特征以及与孩子父亲的关系状态都和内在状态语言的使用有关。研究结果将参考有针对性的干预措施和对未来研究的影响进行讨论。 ملخص: تقييم أثر تدخل عائلي قائم على التمريض على إشارات الأمهات الشابات إلى حالاتهم النفسية الداخلية يعتبر ميل الأم للإشارة إلى الحالات النفسية الداخلية أثناء التفاعلات بين الأم والطفل مهم للنمو المعرفي الاجتماعي لطفلها. ومع ذلك، فإن الأمهات المراهقات أقل احتمالا للإشارة إلى الحالات الداخلية عند التفاعل مع أطفالهن. لقد حققنا فيما إذا كان ميل الأمهات الشابات إلى الإشارة إلى الحالات النفسية الداخلية يزداد من خلال تدخل شراكة العائلة والتمريض (FNP)، وهو برنامج مكثف للزيارات المنزلية يهدف إلى دعم الأمهات المراهقات في المملكة المتحدة. كما قمنا بتحري العوامل الأسرية والأمومية والعوامل المرتبطة بتفاعل الأمهات الشابات مع أطفالهن. شاركت الأمهات المراهقات (العدد = 483، البالغات من العمر ≤ 19 سنة) وأطفالهن في دراسة فرعية قائمة على الملاحظة وهي تجربة معشاة ذات شواهد تبحث في تأثير تدخل شراكة العائلة والتمريض FNP مقارنة بالرعاية المعتادة. تم تسجيل فيديوهات لثنائيات الأم والطفل الفيديو خلال اللعب الحر، وتم ترميز خطاب الأمهات في استخدام لغة الحالة الداخلية (إشارات إلى المعرفة، والرغبات، والعواطف، والنوايا، والتفضيلات، والعوامل الفسيولوجية والإدراك). لم نجد أي اختلافات في استخدام الأمهات للغة الحالة الداخلية بين FNP ومجموعات الرعاية المعتادة. وقد تبين من تحقيق على نطاق العينة أن السمات الأخرى للغة الأمهات وحالة العلاقة مع والد الطفل ترتبط باستخدام لغة الحالة الداخلية. وتناقش النتائج بالإشارة إلى التدخلات المستهدفة وتطبيقات البحوث المستقبلية.